Um estudo sobre bullying entre escolares do ensino fundamental - Francisco, Marcos Vinicius [UNESP]; Coimbra Liborio, Renata Maria [UNESP] (Univ Federal Rio Grande Sul, 2009)
This research, of quali-quatitative nature. had the aim of characterizing the phenomenon of bullying in two state public schools of Presidente Prudente-SP through the use of questionnaires applied to two hundred eighty-three Students of 5(th) and 8(th) grades. It was taken into consideration frequency. gender. most common places and ages of bullying prevalence. students' place of living. effects on the behavior and the feelings of the victim, as well as the opinion of the participants about facing the problem. The questionnaire used was based on studies of Elliot (1992) and Olweus (1991). The results were likely to characterize the dimensions of bullying in the studied reality, what allowed Lis to confirm its presence in the school environment. requesting more attention from the education professionals concerning the phenomenon.
A Study on Bullying Victimization among Peers in Elementary and Junior High School
Keywords: Bullying; violence; students